2018
DOI: 10.1096/fj.201800612r
|View full text |Cite
|
Sign up to set email alerts
|

A young testicular microenvironment protects Leydig cells against age‐related dysfunction in a mouse model of premature aging

Abstract: Testicular Leydig cells (LCs) are the primary source of circulating androgen in men. As men age, circulating androgen levels decline. However, whether reduced LC steroidogenesis results from specific effects of aging within LCs or reflects degenerative alterations to the wider supporting microenvironment is unclear; inability to separate intrinsic LC aging from that of the testicular microenvironment in vivo has made this question difficult to address. To resolve this, we generated novel mouse models of premat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 113 publications
1
13
1
Order By: Relevance
“…The steroids in mouse plasma and testis lysate were measured using an isotope-dilution TurboFlow liquid chromatography-tandem mass spectrometry method as previously described. 14,16 For progesterone, 17-OH-progesterone (17-OHP), androstenedione, and testosterone the limits of quantification were 0.036 nM, 0.1 pM, 0.012 nM, and 0.042 nM, respectively, and the interday variation, expressed as the relative standard deviation for these analytes were testosterone was ≤5.3% and ≤4.2% for low and high spike levels of control materials, respectively, included three times each in every analytical batch. Chemical analyses were performed at the Dept.…”
Section: Hormone Analysismentioning
confidence: 99%
“…The steroids in mouse plasma and testis lysate were measured using an isotope-dilution TurboFlow liquid chromatography-tandem mass spectrometry method as previously described. 14,16 For progesterone, 17-OH-progesterone (17-OHP), androstenedione, and testosterone the limits of quantification were 0.036 nM, 0.1 pM, 0.012 nM, and 0.042 nM, respectively, and the interday variation, expressed as the relative standard deviation for these analytes were testosterone was ≤5.3% and ≤4.2% for low and high spike levels of control materials, respectively, included three times each in every analytical batch. Chemical analyses were performed at the Dept.…”
Section: Hormone Analysismentioning
confidence: 99%
“…Moreover, the aging microenvironment has been shown to dictate stem cell behavior 89 . Similarly, Curley M, et al reported that age-related disruption of the testicular microenvironment or wider endocrine milieu likely plays a critical role in LC dysfunction 90 . To improve the therapeutic effects of SLCs transplantation, we need to develop better ways to rejuvenate aged SLCs in vitro and improve the aging microenvironment in vivo in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…(d) There is de novo recruitment of Leydig cells committed progenitors confirmed at P20 mice having the steroidogenic tissue‐specific deletion of Insr and Igf1r 16 but it remains unknown what happens in the population of mature ALCs, after P80. (e) It was reported that young testicular microenvironment protects Leydig cells against age‐related dysfunction in a mouse model of premature ageing 22 . Besides, the Leydig cells from DKO mice stay in “the previous”/undeveloped stage.…”
Section: Discussionmentioning
confidence: 99%